Dampak Lingkungan Kerja terhadap Tingkat Kepuasan Kerja Pegawai di Badan Pengembangan Sumber Daya Manusia (BPSDM) Provinsi Jambi - Oksa Marani; Dahmiri Dahmiri; Dessy Elliyana (PPIMAN Pusat Publikasi Ilmu Manajemen, 2026)
This study aims to determine and analyze the impact of the work environment on employee job satisfaction at the Human Resources Development Agency (BPSDM) of Jambi Province. The research is motivated by the importance of a supportive work environment in creating comfort, increasing motivation, and improving employee job satisfaction, since preliminary observations found several work-environment problems such as inadequate room cooling, disrupted toilet water supply, and unstable Wi-Fi network. This study used a quantitative approach with an associative research design. The population consisted of 75 employees, all of whom were used as the sample through a saturated sampling technique. Data were collected using a four-point Likert-scale questionnaire and analyzed with validity tests, reliability tests, classical assumption tests, and simple linear regression using SPSS. The results show that the work environment has a significant impact on employee job satisfaction, evidenced by a significance value smaller than 0.05, with a coefficient of determination of 61.8 percent. This indicates that the better the work environment, both physical and non-physical, the higher the employee job satisfaction. This research is expected to serve as a consideration for the agency in improving the quality of the work environment to support employee job satisfaction and performance.